2023
DOI: 10.14569/ijacsa.2023.0140428
|View full text |Cite
|
Sign up to set email alerts
|

Development of Computer Vision-enabled Augmented Reality Games to Increase Motivation for Sports

Abstract: This research paper presents the development of computer vision-enabled augmented reality games based on action detection to increase motivation for sports. With the increasing popularity of digital games, physical activity and sports participation have been declining, especially among the younger generation. To address this issue, we developed a series of augmented reality games that require players to perform physical actions to progress and succeed in the game. These games were developed using computer visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, it has been demonstrated that AR-based instructional digital mo. AR technology has also been used to produce interesting experiences, such as ARbased mobile applications that assist learning in kids with learning disabilities and AR-enabled sports games that increase student motivation for physical activity [23]. AR is essential to transformative learning because it challenges students' preconceived notions and presumptions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that AR-based instructional digital mo. AR technology has also been used to produce interesting experiences, such as ARbased mobile applications that assist learning in kids with learning disabilities and AR-enabled sports games that increase student motivation for physical activity [23]. AR is essential to transformative learning because it challenges students' preconceived notions and presumptions.…”
Section: Literature Reviewmentioning
confidence: 99%